“It's in the Syllabus”: Identifying Information Literacy and Data Information Literacy Opportunities Using a Grounded Theory Approach - Maybee, Clarence; Carlson, Jake; Slebodnik, Maribeth; Chapman, Bert (The Journal of academic librarianship, 2015)
Developing innovative library services requires a real world understanding of faculty members' desired curricular goals. This study aimed to develop a comprehensive and deeper understanding of Purdue's nutrition science and political science faculties' expectations for student learning related to information and data information literacies. Course syllabi were examined using grounded theory techniques that allowed us to identify how faculty were addressing information and data information literacies in their courses, but it also enabled us to understand the interconnectedness of these literacies to other departmental intentions for student learning, such as developing a professional identity or learning to conduct original research. The holistic understanding developed through this research provides the necessary information for designing and suggesting information literacy and data information literacy services to departmental faculty in ways supportive of curricular learning outcomes.